Denitrification Potential of Paddy and Upland Soils Derived From the Same Parent Material Respond Differently to Long-Term Fertilization - Wang, Haicui; Liu, Zhaodong; Ma, Lei; Li, Dandan; Liu, Kailou; Huang, Qinghai; Zhao, Bingzi; Zhang, Jiabao (Frontiers in Environmental Science, 2020)
To investigate the effect of land use and fertilization regimes on soil denitrification potential (SDP), two more than 30-year long-term fertilization experiments derived from same parent material (paddy soil and upland soil) were selected. Generally, the SDP in paddy soil was 6.82 times higher than the upland soil, which was due to the higher abundances of narG, nirS, and nirK genes and nirS-denitrifying bacteria (Bradyrhizobium, Cupriavidus, and Herbaspirillum) in paddy soil. Inorganic fertilization regimes in upland soil did not significantly affect the SDP over Control, while the SDP in NPK and 2NPK of paddy soil decreased by 26.48% and 75.65%, respectively. Compared with Control, NPKOM consistently yielded the highest SDP in both two soils, with 2.47 times and 2.86 times higher for paddy soil and upland soil. The SDP of paddy soil showed correlation with narG and nirS genes mainly regulated by Alo, while the difference in the SDP of upland soil largely depended on the change of nirS-denitrifying bacteria at genus level (Herbaspirillum, Sulfuritalea, and Cupriavidus) and species level, which was mainly controlled by soil pH. PLS path modeling further demonstrated that direct effect of functional genes on the SDP was the greatest for paddy soil, while nirS-denitrifying bacterial communities for upland soil. The results presented herein represent a key step toward understanding the mechanisms that govern SDP under land use and long-term fertilization.